VITAMIN D–BINDING PROTEIN IN HEALTHY PRE- AND POSTMENOPAUSAL WOMEN: RELATIONSHIP WITH ESTRADIOL CONCENTRATIONS - Pop, L. Claudia (Endocr Pract, 2015)
OBJECTIVE: To examine the relationship between endogenous serum estradiol and vitamin D–binding protein (DBP) and total, free, and bioavailable 25-hydroxyvitamin D (25OHD) concentrations in pre- and postmenopausal women. METHODS: In 165 healthy women (ages, 26 to 75 years) not taking any form of exogenous estrogen, the serum concentrations of estradiol, 25OHD, DBP, parathyroid hormone, and albumin were measured. Free and bioavailable 25OHD (free + albumin-bound) levels were calculated from total 25OHD, DBP, and serum albumin levels. RESULTS: Premenopausal women had higher serum 25OHD (31.5 ± 7.9 ng/mL), DBP (45.3 ± 6.2 mg/dL), and estradiol (52.8 ± 35.0 pg/mL) levels than postmenopausal women (26.5 ± 4.9 ng/mL, 41.7 ± 5.7 mg/dL, and 12.9 ± 4.9 pg/mL), respectively. In addition, the calculated free and bioavailable 25OHD levels were higher in pre- than postmenopausal women (P<.05). Serum estradiol correlated with DBP (r = 0.22; P<.01) and total 25OHD (r = 0.27; P<.01). In multivariate regression models (with or without serum 25OHD), estradiol was independently associated with DBP (P<.05). CONCLUSION: Lower estradiol level is one of the factors that contribute to lower DBP levels in older women. Our data indicate that besides well-known factors such as age, gender, and race, serum estradiol concentrations are also a physiologic predictor of DBP concentration.